(untitled) - Huff, W. G. (Cambridge, 1994)
Part one: Themes and beginnings, Part two: Development as a staple port, 1900-1939, Part three: Staple port and rapid growth, 1947-1990.
Keywords: Singapore,Singapore,Chính sách kinh tế,Economic policy,Economic policy; Commerce,Thương mại